Pengembangan Produk Raport Elektronik Automatic Leger & Manuscript Software (ALMaS) dalam Proses Penilaian Belajar Siswa di SMA Nurul Jadid Paiton Probolinggo - Khasanah, Imas; Poernomo, Djoko; S, Suhartono (University of Jember, 2015)
Abstract Global technology increasingly grows rapidly, which demands the Indonesian people to be able to adapt to global technological development. One of technological developments that have been done in the field of education is the product eRaport ALMaS (Automatic Leger and Manuscript Software). eRaport product needs development in order to meet the desires and needs of its users. The development is done on the aspects of Visual Communication Design (DKV), typography, and product features. Analytic Hierarchy Process (AHP) was used to determine the level of interest of the three aspects in accordance with the needs and desires of the users. The research was conducted at SMA (Senior High School) Nurul Jadid Paiton Probolinggo, which utilized this product for 2 years. The analysis obtained Consistency Ratio (CR) of 0.025. CR result was lower than 0.10; thus, the result is said to be consistent, meaning that priority scale can be implemented as a policy to achieve the goals of product development. Based on the calculation, the product feature is the major priority that needs development with a 0.588 scale, the respondent perception feature on eRaport has a lot of lack for example user guidance, analisis statistic and especially on security system. The second priority is DKV with 0.285 scale, this aspects needs to be developed becouse, places of shape is not accords, so user not comfortable with appearance of eRaport. The third priority is Typography with 0.126 scale, selection of shaped and size font was serves need user, so typography aspects in the last priority level than Feature and DKV.